Structural studies with crotoxin B from Crotalus durissus collilineatus venom suggest a heterodimeric assembly formed by two new isoforms - Salvador, Guilherme H.M. [UNESP]; Fernandes, Carlos A.H. [UNESP]; Borges, Rafael J. [UNESP]; Soares, Andreimar M.; Fontes, Marcos R.M. [UNESP] (Elsevier, 2024)
In accidents involving Crotalus snakes, the crotoxin complex (CTX) plays lethal action due to its neurotoxic activity. On the other hand, CTX have potential biotechnological application due to its anti-tumoral, anti-inflammatory, antimicrobial, analgesic and immunomodulatory properties. CTX is a heterodimer composed of Crotoxin A (CA or crotapotin), the acidic nontoxic and non-enzymatic component and; Crotoxin B (CB), a basic, toxic and catalytic PLA2. Currently, there are two classes of CTX isoforms, whose differences in their biological activities have been attributed to features presented in CB isoforms. Here, we present the crystal structure of CB isolated from the Crotalus durissus collilineatus venom. It amino acid sequence was assigned using the SEQUENCE SLIDER software, which revealed that the crystal structure is a heterodimer composed of two new CB isoforms (colCB-A and colCB-B). Bioinformatic and biophysical analyses showed that the toxin forms a tetrameric assembly in solution similar to CB from Crotalus durissus terrificus venom, despite some differences observed at the dimeric interface. By the previously proposed classification, the colCB-B presents features of the class I isoforms while colCB-A cannot be classified into classes I and II based on its amino acid sequence. Due to similar features observed for other CB isoforms found in the NCBI database and the results obtained for colCB-A, we suggest that there are more than two classes of CTX and CB isoforms in crotalic venoms.
Keywords: Crotalus; Crotoxin; Neurotoxin; Phospholipase A2; Quaternary structure; X-ray crystallography